“Being patient through the quiet”: Partnering in problem-based learning in a graduate seminar - Holmes, Ashley J (International Journal for Students as Partners, 2020)
This paper draws connections between scholarship on problem-based learning (PBL) and Students as Partners to frame a case study from a graduate seminar in Public Rhetorics for Social Change. Students partnered with each other and the instructor to decide on a public project, approaching the partnership as a pedagogical problem to explore, discuss, and collaboratively define. Drawing on student and teacher reflections about the partnership, the study’s findings highlight important themes about partnering with students: partnering with students may result in uncertainty and discomfort, takes time, values different perspectives, and can make teachers and students vulnerable to each other. Responding to a phrase from one student’s reflection—“being patient through the quiet”—the study argues that patience and quiet are necessary for supporting a successful partnership with students but that caution is needed to prevent dominant narratives from silencing marginalized student perspectives.